The potential therapeutic role of Lisinopril in augmenting the striatal neuroplasticity via the striatal ACE2/Ang1-7/MAS receptor axis in 3-nitropropionic acid-induced Huntington's disease in rats: shifting paradigms in Huntington's disease treatment - Hanaa Wanas; Mostafa Adel Rabie; Basma Emad Aboulhoda; Nagwa Mahmoud Ramadan; Sahar Abdelwahab; Sara Sayed Kadry Abdallah; Eid Nassar Ali; Leyan Nasruddeen Khayruddeen; Yasir Hassan Elhassan; Hadel Mahroos Alghabban; Shaimaa Mohamed Abdelsalam; Amira Karam Khalifa (SpringerOpen, 2024)
Abstract Background The exact pathogenesis of Huntington's disease (HD) remains unclear. However, mitochondrial dysfunction and oxidative stress are supposed to play a significant role. The objective of this study was to examine the possible neuroprotective effect of Lisinopril (Lisino) in a 3-nitropropionic acid-produced HD in rats. Methods Sixty-four rats were divided into four groups (16/group): Group (1): Normal control group, Group (2): Lisinopril control group, Group (3): 3-NP non-treated group, and Group (4): (3-NP + Lisinopril) group. Behavior assessments (open field test, rotarod test, grip strength test) were performed along with different histological and biochemical parameters. Results Lisinopril upregulated the expression of the ACE2/Ang1-7/MAS receptor (MasR) axis of RAS, which triggered the PI3K/Akt pathway and prompted the CREB/BDNF neurogenesis signal. Furthermore, Lisinopril remarkably downregulated the inflammatory cytokines (NF-κB, TNF-α, IFN-γ and IL-6), decreased apoptotic markers (p53, BAX/Bcl2 ratio, Cyt-c and caspase-3) and upgraded the mitochondrial TFAM content and SDH activity along with restoration of the redox mechanism by recovering SOD, catalase, GSH and Nrf2. Conclusion Notably, the outcomes of this study disclosed that Lisinopril could be a future neuroprotective therapeutic candidate against HD.